Digital-Based Public Service and Its Influence on the Work Environment at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Rokan Hulu Regency - Alvio Nicha; Seno Andri; Adianto Adianto; Zulkarnaini Zulkarnaini (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze the influence of digital-based public services on the work environment at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Rokan Hulu Regency. In the digital era, the transformation of public service delivery has become a strategic necessity to improve efficiency, transparency, and responsiveness in government institutions. The implementation of digital systems is expected not only to enhance service quality for the community but also to significantly affect the internal work dynamics of public institutions. This research employs a qualitative descriptive approach, using interviews, observations, and documentation as data collection techniques. The findings indicate that the adoption of digital public service systems has led to improvements in work efficiency, communication, and employee motivation. However, challenges such as limited digital literacy, inadequate infrastructure, and resistance to change remain critical barriers. The study concludes that while digitalization presents numerous benefits, its success depends on comprehensive strategies including training, infrastructure development, and change management to foster a supportive and adaptive work environment.